Efficacy of Ocular Vestibular-Evoked Myogenic Potential in Identifying Posterior Semicircular Canal Benign Paroxysmal Positional Vertigo. Issue 2 (March 2015) - Singh, Niraj Kumar; Barman, Animesh
<x xml:space="preserve">Abstract</x> Objectives: Benign paroxysmal positional vertigo (BPPV) is a unilateral peripheral vestibular pathology, mostly involving the semicircular canals and the otolith organs. Although equivocal findings exist on the utility of cervical vestibular-evoked myogenic potential in identifying BPPV-associated changes in saccule, ocular vestibular-evoked myogenic potential (oVEMP), which is primarily a utricular response, has sparingly been explored in this population. Hence, the present study aimed at examining oVEMP in individuals with BPPV and comparing them with healthy individuals to illustrate its efficacy in identifying BPPV-associated changes in the utricle. Design: Using a case-control design, oVEMPs were elicited by 500 Hz tone bursts at 125 dB peak sound pressure level and recorded bilaterally from 30 individuals with unilateral posterior canal BPPV and 30 age- and gender-matched healthy controls. Results: There were no inter- or intragroup differences in latency aspects (p > 0.05); however, amplitudes were significantly smaller in BPPV ears compared with the non-BPPV ears of individuals with BPPV as well as ears of healthy controls (p < 0.05). Exceptions to this were five participants with BPPV in whom the affected ears demonstrated larger response amplitude (augmentation) than the unaffected ears. Furthermore, there was significantly larger interaural amplitude ratio in individuals with BPPV compared with the healthy controls (p < 0.05). Interaural amplitude ratio produced the largest effect size among the oVEMP parameters for differentiating BPPV from healthy controls. Conclusions: Large asymmetry ratio of oVEMP, usually exceeding 26.8%, is the most potent characteristic of oVEMP in BPPV. Abnormal oVEMP results confirm utricular pathology in ears with BPPV, and therefore, oVEMP can be used as an objective tool with asymmetry ratio as the parameter of choice for the evaluation of utricular function in persons with posterior canal BPPV.